Schornikovoecia eugenyi, a novel species and genus of deep benthopelagic halocyprids (Ostracoda, Myodocopa) from the North-west Pacific - Chavtur, Vladimir G.; Bashmanov, Alexander G. (Zootaxa, 2018)
Schornikovoecia eugenyi gen. et sp. nov. of the benthopelagic ostracods of the subfamily Bathyconchoeciinae is established and described, based upon samples collected in the deep-sea zones near the Kurile-Kamchatka Trench and in the Sea of Okhotsk (Kurile Hollow). Most of the specimens have been found at depths over 5000 m. The new genus differs sharply from the currently known genera Bathyconchoecia, Scottoecia, Bathyconchoecetta and Septemoecia of this subfamily in numerous ways: the singular sculpture; the form and structure of the glands on the carapace; the masticatory pad on the mandible; the arming of the fifth limb. The new genus is at present monospecific. Descriptions of the new genus and its new species S. eugenyi sp. nov. are presented.